A community-based survey of Toxoplasma gondii infection among pregnant women in rural areas of Taiz governorate, Yemen: the risk of waterborne transmission - Mahdy, Mohammed A. K.; Alareqi, Lina M. Q.; Abdul-Ghani, Rashad; Al-Eryani, Samira M. A.; Al-Mikhlafy, Abdullah A.; Al-Mekhlafi, Abdulsalam M.; Alkarshy, Fawzya; Mahmud, Rohela (BioMed Central (BMC), Springer Nature, 2017)
Background Toxoplasma gondii is a zoonotic coccidian parasite causing morbidity and mortality. In Yemen, T. gondii infection has been reported among pregnant women seeking healthcare in the main cities. However, no data are available on the prevalence of T. gondii infection and its associated risk factors among pregnant women in the rural communities of the country. Thus, the present study aimed to determine the seroprevalence of T. gondii and identify its risk factors among pregnant women in the rural communities of Taiz governorate, Yemen. Methods A total of 359 pregnant women living in the rural communities of Taiz governorate were enrolled in this study by house-to-house visits. Data were collected using a pre-designed questionnaire, and blood samples were collected and tested for the detection of anti- T. gondii IgM and IgG antibodies by enzyme-linked immunosorbent assay. Results The prevalence of T. gondii infection among pregnant women in this study was 46.2% (166/359). Bivariate analysis identified the age of ???30 years (odds ratio [OR]?=?1.7; 95% confidence interval [CI]?=?1.09-2.65, P?=?0.019) and unimproved water sources (OR?=?2.2; 95% CI?=?1.10-4.55, P?=?0.023) as factors associated with T. gondii infection among pregnant women. The multivariable analysis, however, identified unimproved water sources as an independent risk factor (adjusted OR?=?2.4; 95% CI?=?1.16-5.0, P?=?0.018) associated with T. gondii infection among pregnant women. Conclusions Pregnant women in the rural communities of Taiz, Yemen are at high risk of contracting T. gondii infection. Unimproved water sources (wells, water streams and water tanks) are significantly associated with T. gondii infection and should be considered in prevention and control strategies, especially among pregnant women.